Bacterial-type ferredoxin genes in the nitrogen fixation regions of the cyanobacterium Anabaena sp. strain PCC 7120 and Rhizobium meliloti. - Mulligan, M E (1988)
The nucleotide sequence of a region located downstream of the nifB gene, both in the cyanobacterium Anabaena sp. strain PCC 7120 and in Rhizobium meliloti, has been determined. This region contains a gene (fdxN) whose predicted polypeptide product strongly resembles typical bacterial ferredoxins. Cyanobacteria have not previously been shown to contain bacterial-type ferredoxins. The presence of this gene suggests that nitrogen-fixing cyanobacteria have at least four distinct ferredoxins.